Copolymer‐Mediated Cell Aggregation Promotes a Proangiogenic Stem Cell Phenotype In Vitro and In Vivo. Issue 22 (26th September 2016) - Crowder, Spencer W.; Balikov, Daniel A.; Boire, Timothy C.; McCormack, Devin; Lee, Jung Bok; Gupta, Mukesh K.; Skala, Melissa C.; Sung, Hak‐Joon
Abstract : Material‐induced cell aggregation drives a proangiogenic expression profile. Copolymer substrates containing cell‐repellent and cell‐adhesive domains force the aggregation of human mesenchymal stem cells, which results in enhanced tubulogenesis in vitro and stabilization of vasculature in vivo. These findings can be used to design instructive biomaterial scaffolds for clinical use.